Investigating Optimal Autologous Cellular Platforms for Prenatal or Perinatal Factor VIII Delivery to Treat Hemophilia A - Stem, Christopher; Rodman, Christopher; Ramamurthy, Ritu M.; George, Sunil; Meares, Diane; Farland, Andrew; Atala, Anthony; Doering, Christopher B.; Spencer, H. Trent; Porada, Christopher D.; Almeida-Porada, Graça (Frontiers in Cell and Developmental Biology, 2021)
Patients with the severe form of hemophilia A (HA) present with a severe phenotype, and can suffer from life-threatening, spontaneous hemorrhaging. While prophylactic FVIII infusions have revolutionized the clinical management of HA, this treatment is short-lived, expensive, and it is not available to many A patients worldwide. In the present study, we evaluated a panel of readily available cell types for their suitability as cellular vehicles to deliver long-lasting FVIII replacement following transduction with a retroviral vector encoding a B domain-deleted human F8 transgene. Given the immune hurdles that currently plague factor replacement therapy, we focused our investigation on cell types that we deemed to be most relevant to either prenatal or very early postnatal treatment and that could, ideally, be autologously-derived. Our findings identify several promising candidates for use as cell-based FVIII delivery vehicles and lay the groundwork for future mechanistic studies to delineate bottlenecks to efficient production and secretion of FVIII following genetic-modification.